Analisis Strategi Manajemen Pendidikan Mutu SDM PAI: Pendekatan Integratif untuk Optimalisasi Layanan Pendidikan Agama Islam - Ika Fiisyatil Kamila; Ali Nurhadi; Juhairiyah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The quality of educators and human resources (HR) is a fundamental element in achieving the goals of high-quality Islamic Religious Education (PAI). This article aims to analyze management strategies for improving the quality of personnel and HR in the PAI sector through an integrative approach. The research method employed is a descriptive qualitative approach, using literature review from various primary and secondary sources. The analysis reveals that effective strategies include competency-based recruitment, continuous training, regular performance evaluation, and the implementation of an innovative work culture. These findings are expected to serve as a strategic reference for enhancing the quality of PAI personnel across educational institutions.